OPTIMIZATION OF PROPHYLAXIS OF HYPERCOAGULATION COMPLICATIONS IN ONCOLOGICAL SURGERY - A. M. Karsanov; S. S. Maskin; A. A. Kul’Chiev; F. D. Karsanova; T. R. Karaev; G. K. Mil’Dzikhov (Вестник хирургии имени И.И. Грекова, 2018)
The authors investigate the results of prophylaxis of venous thromboembolic complications (VTC) during 24 years in oncological surgery. The multicentric study shows that common frequency of occurrence of such VTC was reduced due to period of routine prophylaxis of VTC to 3,4%. The strategy of active revision and escalation of preventive measures in the third period of study in comparison with the second period resulted in the decrease of VTC. Patients with moderate risk degree had the results from 3,2% to 1%, patients with high risk degree moved from 4,1% to 1,3%. The fatal thromboembolism of the lung artery was 0,1%.